Self-assessment of cochlear health by cochlear implant recipients - Mushtaq, Faizah; Soulby, Andrew; Boyle, Patrick; Nunn, Terry; Hartley, Douglas E. H. (Frontiers in Neurology, 2022)
Recent technological advances in cochlear implant (CI) telemetry have enabled, for the first time, CI users to perform cochlear health (CH) measurements through self-assessment for prolonged periods of time. This is important to better understand the influence of CH on CI outcomes, and to assess the safety and efficacy of future novel treatments for deafness that will be administered as adjunctive therapies to cochlear implantation. We evaluated the feasibility of using a CI to assess CH and examined patterns of electrode impedances, electrically-evoked compound action potentials (eCAPs) and electrocochleography (ECochGs), over time, in a group of adult CI recipients. Fifteen subjects were trained to use the Active Insertion Monitoring tablet by Advanced Bionics, at home for 12 weeks to independently record impedances twice daily, eCAPs once weekly and ECochGs daily in the first week, and weekly thereafter. Participants also completed behavioral hearing and speech assessments. Group level measurement compliance was 98.9% for impedances, 100% for eCAPs and 99.6% for ECochGs. Electrode impedances remained stable over time, with only minimal variation observed. Morning impedances were significantly higher than evening measurements, and impedances increased toward the base of the cochlea. eCAP thresholds were also highly repeatable, with all subjects showing 100% measurement consistency at, at least one electrode. Just over half of all subjects showed consistently absent thresholds at one or more electrodes, potentially suggesting the existence of cochlear dead regions. All subjects met UK NICE guidelines for cochlear implantation, so were expected to have little residual hearing. ECochG thresholds were, unsurprisingly, highly erratic and did not correlate with audiometric thresholds, though lower ECochG thresholds showed more repeatability over time than higher thresholds. We conclude that it is feasible for CI users to independently record CH measurements using their CI, and electrode impedances and eCAPs are promising measurements for objectively assessing CH.